2007
DOI: 10.1007/bf02685907
|View full text |Cite
|
Sign up to set email alerts
|

Dose dense (CEOP-14) vs dose dense and rituximab (CEOP-14+R) in high-risk diffuse large cell lymphoma

Abstract: To assess efficacy and toxicity of rituximab and dose chemotherapy in high-risk diffuse large cell lymphoma, we conducted a controlled clinical trial to assess efficacy and toxicity of a dose-dense regimen CEOP- 14 (cyclophosphamide, epirubicin, vincristine, and prednisone every 14 d) compared to CEOP-14 plus rituximab. One hundred and ninety-six patients were randomized to received CEOP-rituximab (cyclophosphamide 1500 mg/m2, epirubicin 120 mg/m2, vincristine, and prednisone at standard dose and rituximab at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Many reactions developed within 24 hours of the first infusion, were dose-dependent, and were often more common in those who received rituximab versus those receiving the conventional chemotherapy regimen [4,14,37-39]. The frequency of the reactions decreased with subsequent cycles, and life-threatening anaphylaxis was rare [14,36,40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reactions developed within 24 hours of the first infusion, were dose-dependent, and were often more common in those who received rituximab versus those receiving the conventional chemotherapy regimen [4,14,37-39]. The frequency of the reactions decreased with subsequent cycles, and life-threatening anaphylaxis was rare [14,36,40].…”
Section: Resultsmentioning
confidence: 99%
“…However, cytopenia was more common in chemotherapy trials of regimens in which rituximab was combined with agents more frequently associated with myelosuppression [39,45,46]. For example, granulocytopenia (grades 3 and 4) occurred in 72% of R-CHOP-treated patients compared with 57% of CHOP-treated patients in 64 patients with lymphoplasmacytic lymphoma/Waldenström macro-globulinemia [45].…”
Section: Resultsmentioning
confidence: 99%
“…Rituximab is a monoclonal antibody against the B-cell marker CD20 and is used in a variety of conditions including lymphoproliferative disorders and autoimmune diseases [1, 2, 3]. Rituximab is usually well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they suggested that R cannot be employed in this clinical situation. 13,14 Maintenance therapy has been employed after induction regimens in DLBCL and has used low doses of cytotoxic drugs, 15 interferon after standard CHOP, 16 and with the use of intensive or dose-dense regimens, [17][18][19] induction of graftversus-host disease, 20 SCT after CHOP or R-CHOP 21 ; however, no clear benefit has observed. On the other hand, late toxicities continue to be a problem that can be intensified with the use of maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%